SUPERVISI MANAJERIAL UNTUK MENINGKATKAN MUTU PENYELENGGARAAN PENDIDIKAN SEKOLAH DASAR DI ERA SOCIETY 5.0 - Ramadina, Evy (Jurnal Manajemen Pendidikan, 2024)
The positive image of educational institutions is formed because of public trust, especially users of educational services who are satisfied with the provision of education they receive. Providing quality education will have an impact on the satisfaction of users of educational services. The method used in writing this study is literature. This research is a type of research that collects data from literature. The data collection technique in this research is documentation, namely looking for written sources that contain information on the topic being discussed. Educational institutions, especially elementary schools, must always create, develop and maintain quality educational services, so that they are able to survive as educational institutions that are oriented towards the needs of educational service users. In the era of society 5.0, elementary schools must be able to solve various social challenges and problems by utilizing educational innovation and technology. To ensure the quality of comprehensive and sustainable education delivery, managerial supervision is required. The use of this technology has an impact on making education easier to access, can reach a wider range of educational service users, makes it easier for students to achieve their competencies, and stimulates students' critical thinking abilities.